A BRAF new world. (August 2020) - Frisone, Daniele; Friedlaender, Alex; Malapelle, Umberto; Banna, Giuseppe; Addeo, Alfredo
Abstract: BRAF is a rare targetable mutation in non-small-cell lung cancer (NSCLC). Emerging evidence underlines that, rather than a single point mutation, BRAF genes present with a wide array of mutations, essentially in lung adenocarcinoma. Different BRAF mutations have divergent clinical and therapeutic implications, with a particular distinction between V600E and non-V600E mutations. The latter are at least as frequent in NSCLC as V600E, but lack any proven targeted therapy. In this paper, we briefly review the current literature and provide an update of scientific knowledge about different types of BRAF mutations in NSCLC.